Relações Públicas e comunicação organizacional: um estudo sobre as publicações científicas da Associação Brasileira de Pesquisadores de Comunicação Organizacional e Relações Públicas - Abrapcorp - Simões, Julie Anne Janio (Brasil, 2023)
The main objective of the research carried out is to analyze the theoretical perspective established by the authors on public relations and organizational communication, based on scientific publications in the Annals of the Brazilian Association of Organizational Communication and Public Relations Researchers-Abrapcorp, from 2008 to 2018 To carry out the project, exploratory, descriptive and explanatory research was used, with a focus on quantitative and qualitative approaches. The identification of articles that contain their keywords, respectively, “public relations” and “organizational communication”, published in the defined period, was carried out. The research results show that in the period, twenty-seven (27) works published in the Annals of Abrapcorp were identified, the year 2016 is considered the most prosperous in publications on the subject, the years 2012 and 2014 a significant reduction in publications. It was found that the Southeast region had greater representativeness of authors, as they considered public relations and organizational communication more often in their themes, it is noteworthy that researchers from the North region did not publish in this period. Finally, when analyzing the theoretical perspective of the authors, most scientific publications of the not deal with public relations and organizational communication in an interdependent way, as the areas exist independently of each other, however, they believe that acting in the environment A professional cooperative way can bring measurable benefits to organizations, because both areas are concerned with effectively managing the relationships between organizations and their audiences.